Evidence map of traditional Chinese exercises - Yan Yu; Tongtong Wu; Murou Wu; Shaonan Liu; Shaonan Liu; Xueyin Chen; Jinpeng Wu; Xinfeng Guo; Xinfeng Guo; Lihong Yang (Frontiers Media S.A., 2024)
ObjectiveThis study aimed to assess and visually depict the clinical evidence landscape of traditional Chinese exercises and identify any research gaps and future research needs.MethodsWe comprehensively searched seven Chinese and English databases to identify randomized controlled trials (RCTs) and systematic reviews (SRs) evaluating the effects of traditional Chinese exercises from their inception until May 2023. The quality of evidence was assessed via the GRADE approach, and the research topics, intervention effects, and strength of evidence were graphically displayed.ResultsThis evidence map includes 2,017 studies, comprising 1,822 RCTs and 195 SRs. These studies were conducted globally in various countries. Among the traditional Chinese exercises, Tai Chi and Baduanjin have received the most research attention, with a growing number of publications. When traditional Chinese exercises were compared with the control groups, 88.2% of the included SRs reported significantly positive effects, 4.1% reported unclear effects, and 7.7% reported no significant differences. The findings suggested that traditional Chinese exercises could benefit patients with osteoarthritis, osteoporosis, hypertension, coronary heart disease, diabetes, chronic obstructive pulmonary disease, stroke, Parkinson's disease, anxiety, and depression. However, the overall quality of the evidence was suboptimal, with 11.3% rated as moderate, 45.6% as low, and 43.1% as critically low.ConclusionThis evidence map visually represents valuable information on traditional Chinese exercises. While most studies have reported significant benefits, the overall quality of evidence is low.